Mac Programming for Absolute Beginners - Wang, Wallace; SpringerLink (Online service) (Berkeley, CA : Apress : Imprint: Apress, 2011)
Want to learn how to program on your Mac? Not sure where to begin? Best-selling author Wallace Wang will explain how to get started with Cocoa, Objective-C, and Xcode. Whether you are an experienced Windows coder moving to the Mac, or you are completely new to programming, you$1 (Bll see how the basic design of a Mac OS X program works, how Objective-C differs from other languages you may have used, and how to use the Xcode development environment. Most importantly, you$1 (Bll learn how to use elements of the Cocoa framework to create windows, store data, and respond to users in your own Mac programs. If you want to learn how to develop apps with Cocoa, Objective-C, and Xcode, this book is a great first step. Here are just a few of the things you$1 (Bll master along the way: Fundamental programming concepts aided by short, easy-to-understand examples How to use Xcode and related programming tools to save time and work more efficiently A firm understanding of the basics of Objective-C and how it compares to other languages you might know How to create simple apps using the Cocoa framework How to easily design, write, test, and market your finished program With this book and your trusty Mac, you$1 (Bre well on your way to transforming your Mac app ideas into real applications.s
Keywords: Computer science; Software engineering; Computer Science; Computer Science, general; Software Engineering/Programming and Operating Systems